(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2015)
Ectopic means "out of place." In a normal pregnancy, the fertilized egg implants and develops in the uterus. In most ectopic pregnancies, the egg settles in the fallopian tubes. This is why ectopic pregnancies are commonly called "tubal pregnancies." None of these areas has as much space or nurturing tissue as a uterus for a pregnancy to develop. As the fetus grows, it will eventually burst the organ that contains it This can cause severe bleeding and endanger the mother’s life. A classical ectopic pregnancy does not develop into a live birth. The tube is capable for only limited distention and is unable to provide secure placentation also due to unsatisfactory environment, 80% of these embryo are malformed and more than 99% of these do not progress beyond 6 weeks of pregnancy. A 25 years lady para 1+1 (Ectopic pregnancy) present as an emergency patient with history of pregnancy of 4 months with shock immediate resuscitation, intubation and laparotomy was done for high intuition towards ectopic pregnancy. It was great surprised that there was a near about 16 weeks size of foetus coming out from the ruptured tube and the tube was hugely distented about 10 cm diameter. After laparotomy the patient was recovered well. The case is reported here as a very rare entity and near miss mortality. JCMCTA 2015 ; 26 (1) : 59-62